Tinjauan Pengenanaan PPh Final Atas Usaha Persewaan lapangan Badminton Perum Bulog Di Makassar - A. Faisal Setiawan Mus; Ilham Ilham; Mahardian Hersanti Paramita (PT Bone Jaya Kreatif, 2022)
Taxes on business income from badminton field rental are one of the objects of income tax. According to the definition of Law Number 36 of 2008 concerning income tax, income is any additional economic ability received or obtained by taxpayers, both from Indonesia and from outside Indonesia, which can be used for consumption or to increase the taxpayer's wealth. by name and in any form so that the income is subject to tax which must be paid to the State. Because the income is taxed, the taxpayer's active role is required in carrying out tax obligations based on the self assessment system. This study aims to determine the imposition of Final Income Tax Article 4 paragraph (2) on Badminton Field Rental Perum Bulog Divisi Regional SulSelBar Di Makassar. The research method used in this study is a Qualitative Descriptive Method by conducting interviews with the Taxation staff of the Regional Division of the National Logistics Agency, SulSelBar. The data used in this study is primary data in the form of gross circulation data on field rental business. The results of the research show that income from the Badminton Field Rental Perum Bulog Divisi Regional SulSelBar At Makassar is subject to Final Income Tax Article 4 paragraph (2) at a rate of 1% and the imposition of Final Income Tax is based on gross circulation of the business within 1 (one) tax year. Perum Bulog does calculations and rates according to Law No. 36 of 2008 concerning Income Taxes.